2001
DOI: 10.1159/000051707
|View full text |Cite
|
Sign up to set email alerts
|

Marginal Papular Acrokeratodermas: No Racial Limitations for a Clinical Spectrum That Responds to Acitretin

Abstract: Marginal papular acrokeratoderma (MPA) encompasses a group of disorders that share crateriform, keratotic papules along the margins of the hands and feet. We report a unique case of a Philippino woman, with focal acral hyperkeratosis (FAH) associated with sensorineural hearing loss. The clinical phenotype of FAH (hereditary MPA without elastorrhexis) is expanded and the hypothesis of a racially limited disorder is weakened. Effective treatment of this embarrassing condition with acitretin is demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 7 publications
0
10
0
1
Order By: Relevance
“…It is one of the rare groups of diseases that are believed to be due to some unknown pathophysiological process where genetic variations or heredity may be one of the main causal factors. AKE was believed to have a racial predilection towards Arabs and Negroes; although this hypothesis has been challenged [3]. …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is one of the rare groups of diseases that are believed to be due to some unknown pathophysiological process where genetic variations or heredity may be one of the main causal factors. AKE was believed to have a racial predilection towards Arabs and Negroes; although this hypothesis has been challenged [3]. …”
Section: Introductionmentioning
confidence: 99%
“…For the differential diagnosis of AKE, focal acral hyperkeratosis has a similar clinical appearance, but during histopathological examination, elastorrhexis is not seen and alterations are confined to the epidermis (hyperkeratosis and acanthosis) [3]. Another condition with a similar clinical appearance to AKE is marginal keratoelastoidosis, which is generally associated with intense sun exposure, marked actinic damage, and genetic inheritance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the rarity of the condition, treatment recommendations are mainly based on single cases. Several reports on the efficacy of acitretin or other systemic retinoids in marginal papular acrokeratodermas have been published recently [4,17,18]. However, the potential teratogenicity of this therapy should always be taken into consideration in young patients with AKE.…”
mentioning
confidence: 99%
“…A recent study showed a slight improvement by treating with topical salicylic acid or topical retinoids, although there were generally recurrences after discontinuation of treatment. 4 It is considered that these topical treatments do not improve dermal elastolytic change. Our case has not been recurrent because he continued to apply 10% salicylic acid ointment.…”
mentioning
confidence: 99%